Adiponectin and Disease Severity in Sickle Cell Anemia Patients Attending a Tertiary Health Institution in Nnewi, Southeast Nigeria - Okocha, Chide Emmanuel; Manafa, Patrick O.; Igwe, Chioma Nkechinyere; Okite, Uchechukwu Prince; Onah, Christian Ejike; Efobi, Chilota (Frontiers in Genetics, 2022)
Background: Hemoglobin polymerization in Sickle Cell Anemia (SCA) leads to abnormally rigid and adhesive erythrocytes that obstruct blood vessels, leading to poor tissue perfusion; hence provoking inflammation and damage of surrounding tissues. Adiponectin, a protein hormone, presumptively has anti-inflammatory characteristics; hence may be an important therapeutic target in SCA. Aim: To evaluate the status of adiponectin and its correlation with disease severity in SCA. Patients and Methods: 84 subjects were recruited for the study comprising 34 homozygous sickle cell (HbSS) subjects (25 in steady state and 9 in resolving crisis state) and 50 controls (25 heterozygous sickle cell [HbAS] and 25 hemoglobin phenotype AA subjects). The hemoglobin phenotype, adiponectin levels, and full blood counts, were evaluated. Anthropometric measurements were also conducted. Results: A significant difference was observed in the mean body mass index between the different hemoglobin phenotype groups; also, between the SCA in crisis resolution patients and the control group (p<0.05). There was no significant difference in the median serum levels of Adiponectin in the different hemoglobin phenotype groups and between SCA patients in steady state compared with crisis resolution state. Also, there was no correlation between disease severity and adiponectin in SCA patients in steady state (p=0.87). Conclusion: Our study seems to suggest that in our data set of sickle cell anemia patients in steady state, adiponectin does not constitute part of the endocrinopathy that these patients have.